The science behind programming algorithms for sacral neuromodulation - Knowles, Charles H.; De Wachter, Stefan; Engelberg, Stefan; Lehur, Paul; Matzel, Klaus E.; Zirpel, Lance (Colorectal Disease, 2020)
Aim Sacral neuromodulation (SNM) is a widely adopted treatment for overactive bladder, non-obstructive urinary retention and faecal incontinence. In the majority, it provides sustained clinical benefit. However, it is recognized that, even for these patients, stimulation parameters (such as amplitude, electrode configuration, frequency and pulse width) may vary at both initial device programming and at reprogramming, the latter often being required to optimize effectiveness. Although some recommendations exist for SNM programming, the scientific data to support them are understood by few clinicians.
CRIS-Team WoS Importer:2020-11-13